PENGARUH KUALITAS LAYANAN, MINAT BELI DAN KEPUASAN PELANGGAN DALAM MEMBENTUK LOYALITAS PELANGGAN - Muhammad Faisyal Nurkhalik (Ekonam: Jurnal Ekonomi, Akuntansi & Manajemen, 2020)
Abstrac This study aims to determine the effect of Service Quality, Buying Intention, and Customer Satisfaction factors on Rumah Makan Sop Kaki 999 Bandung Khas Mas Udin , this type of research uses a qualitative approach. the population of this study is Rumah Makan Sop Kaki 999 Bandung Khas Mas Udin consumers, and the samples used in this study were 62 respondents where data collection methods using a questionnaire, data analysis in this study uses the SPSS application, namely multiple linear regression analysis with the equation Y = a + b1x1 + b2x2 + b3x3. Based on the results of the analysis that has been described in the results obtained that the variable X1 Service Quality, variable X2 Buying Intention, and variable X3 Customer Satisfaction significantly influence the variable Y Consumer Loyalty decisions on Rumah Makan Sop Kaki 999 Bandung Khas Mas Udin. By 88.6% while the rest is influenced by other variables not research in this study. With a regression equation Y = 1,022 + 0,222 X1 + 0,721 X2 + 0,024 X3. Keywords:Service Quality Factors, Buying Intention,Customer Satisfaction